2017
DOI: 10.18488/journal.68.2017.41.14.31
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Agricultural Productivity to Enhance Economic Growth in Botswana

Abstract: The need to diversify the economy so as to ensure sustainable economic growth has been of great concern. Accelerating productivity in agriculture is seen as one of the alternatives to support the diversification initiatives by the government and drive growth in Botswana. This study discusses the factors contributing to increased long term agricultural productivity and hence its subsequent impact on growth in the short. The study employs the vector error correction model and annual data to explain the connectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, there is no significant impact observed for labor employed in agriculture. Mbulawa (2017), study focused on the factors that contribute to long-term agricultural productivity and their subsequent impact on short-term growth. The author utilized the vector error correction model and annual data to establish the relationship between key variables.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
“…However, there is no significant impact observed for labor employed in agriculture. Mbulawa (2017), study focused on the factors that contribute to long-term agricultural productivity and their subsequent impact on short-term growth. The author utilized the vector error correction model and annual data to establish the relationship between key variables.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
“…Scholars such as utilised the VECM model and found that electricity supply boosts economic growth in South Africa on time series data spanning from 1990 to 2012 citing to the fact that models does not necessarily matter when it come to the relationship between the variables. Adebola (2011), Amusa andLeshoro (2013), andOdhiambo (2021) utilised ARDL model while Mbulawa (2017), Chingoiro and Mbulawa (2017) and Sunde (2020) utilised a VECM and VAR models respectively to analyse the relationship between the variables in Botswana. These studies found a positive relationship and unidirectional causality between electricity consumption and economic growth emphasizing that electricity is important for the growth of an economy.…”
Section: Studies From Sadc Regionmentioning
confidence: 99%
“…Agriculture food deficit draws down reserves for the country (Mazonde, 1993;and Jefferis and Nemaorani, 2014). There is need to improve production skills so as to increase agriculture output (Mbulawa, 2017). Of note is that livestock rearing is Botswana's key agricultural output and export (Makoni, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With a decrease in international mineral prices and depletion of the nonrenewable mining resources, the need to diversify the economy so as to ensure sustainable economic growth has been of great concern. Accelerating productivity in agriculture is seen as one of the alternatives to support the diversification initiatives by the government and drive growth in Botswana (Mbulawa, 2017). Mbulawa (2017) investigated the relationship between agriculture productivity and economic growth in Botswana.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation